Did Germany reach its 2020 climate targets thanks to COVID-19? - Shivenes Shammugam; Joachim Schleich; Barbara Schlomann; Lorenzo Montrone (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
In this paper, we estimate the effects of COVID-19 on greenhouse gas emissions (GHG) in Germany in 2020 at the sectoral and national level. Counterfactual emissions are estimated based on autoregressive econometric models and distinguish between different factors of emissions based on decomposition analysis. Our findings at the national level suggest that COVID-19 lowered GHG emissions in 2020 in Germany by about 45 Mt CO2-eq (6.1%). Accordingly, about two-thirds of the reduction in emissions between 2019 and 2020 in Germany may be attributed to COVID-19. Our findings at the sectoral level imply that all sectors, with the exception of the transport sector, would have met their emissions target in 2020 without COVID-19. Thus, for the buildings sector and the transport sector, our results suggest policy responses that differ from those pursued by the German government to comply with the provisions of the Federal Climate Change Act.
urn:nbn:de:0011-n-6403749
Keywords: 330; COVID-19; climate targets; climate policy; greenhouse gas emissions